A Selectivity Evaluation on Mackerel (Rastrelliger kanagurta) Encircling Gillnet in Coastal Water of Ambon Island - Sangadji, Selfi; Haruna, Haruna; Tupamahu, Agustinus; Noija, Donald (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2022)
This research aims to analyze selectivity to mackerel (Rastrelliger kanagurta) encricling gill net in costal area of Ambon Island. Fish sample was taken by following the whole series of capture fisheries operation by fishermen at two units of the encircling gillnet using both 2.0 and 2.5 inch mesh size. Holt method was used to analyze and predict selectivity of the mesh size operated by fishermen towards total length of mackerel. Dominant composition of the capture fisheries was in mackerel at 69.29% of seven fish species. Distribution of total length at mesh size 2.0 inch at the middle size of 21.5 cm - 25.5 cm and 2.5 inch at the middle size of 22.5 cm - 31.5 cm. Mesh length tended to be normally distributed, while length proportion for large size was higher in mesh size at 2.5 inch. For capture possibility at proportion 50% and optimum (100%) at mesh size at 2.0 inch was 19.9 cm and 21.9 cm, while mesh size at 2.5 inch was 25.4 cm and 27.4 cm. It is recommended to use minimum mesh size at 2.5 inch towards the resource of mackerel in coastal area of Ambon Island. Distribution of total length at mesh size 2.0 inch at the middle size of 21.5 cm - 25.5 cm and 2.5 inch at the middle size of 22.5 cm - 31.5 cm. Mesh length tended to be normally distributed, while length proportion for large size was higher in mesh size at 2.5 inch.